citra satellite The changes in mangrove land cover area using satellite image data in South Manokwari District, Manokwari Regency.: Perubahan Luasan Manggrove Menggunakan Data Citra Satelit di Distrik Manokwari Selatan Kabupaten Manokwari - Irnawati, Irnawati; Milangoni, Elok; Febriadi, Ihsan; Soekamto, Mira Herawati (Universitas Muhammadiyah Sorong, 2024)
Mangroves are one of the defining characteristics of transitional plants between the sea, water bodies, and land. They are only found in tropical and subtropical regions with some extreme conditions such as high salt content, high temperatures, high waves, sedimentation, and mud. The distribution of mangroves in Indonesia with the highest dense cover is in Papua Province with a total area of ​​1,084,514 hectares, and West Papua Province has mangrove forests with a total area of ​​483,800 hectares, 76% of which are primary mangrove forests and the rest are secondary mangrove forests (24%). One method to determine changes in the area of ​​mangrove vegetation is remote sensing technology aimed at identifying changes in the mangrove area covered by the mangrove ecosystem over different periods as potential forest resources using Composite image software ER Mapper series 6.4. Research results During the period 2014 - 2023, there has been a change in the area of ​​mangroves in South Manokwari District with a degraded mangrove forest area of ​​53,767 hectares, with a deforestation area of ​​5,974 hectares per year. In the same period, forest degradation of 43,442 hectares also occurred with a degradation area per year of 4,827 hectares. The accuracy level value of Landsat satellite image classification for changes in mangrove area in South Manokwari District, Manokwari Regency in 2014, 2017, 2020, and 2023 reached 92.5%, which means it is quite accurate